Symulacyjne porównanie jakości modeli otrzymanych metodą wektorów nośnych z innymi modelami regresji - Trzęsiok, Michał (Benchmarking support vector machines against other regression methods, 2007)
For nonlinear regression problem, support vector machines (SVM) map the input space into a high-dimensional feature space first, and then perform linear regression in the high-dimensional feature space. The paper presents the comparison of SVM and other regression methods (linear regression, Projection Pursuit Regression, Neural Networks, Regression Trees, Random Forest, Bagging) by the means of mean squared test set error.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 234-241